Strategy for salvaging infected breast implants: lessons from the recovery of seven consecutive patients - Hyeonjung Yeo; Dongkyu Lee; Jin Soo Kim; Pil Seon Eo; Dong Kyu Kim; Joon Seok Lee; Ki Tae Kwon; Jeeyeon Lee; Ho Yong Park; Jung Dug Yang (Archives of Plastic Surgery, 2021)
Background In recent years, implant-based breast reconstruction has been performed because of its simplicity, short operation time, and rapid recovery of patients. Several studies have reported treatment methods for implant surgery-related infection, which is a serious complication. The aim of this study was to introduce our strategy for salvaging infected implants and to evaluate its effectiveness. Methods The authors performed a retrospective study of 145 cases from 132 patients who underwent implant-based breast reconstruction from January 2012 to December 2018. Empirical antibiotics were immediately administered to patients with suspected infections. The patients then underwent salvage treatment including appropriate antibiotics, ultrasonography-guided aspiration, debridement, antibiotic lavage, and implant exchange through a multidisciplinary approach. Patient demographics, operative data, duration until drain removal, adjuvant treatment, and complications were analyzed. Results The total infection rate was 5.5% (8/145). A longer indwelling catheter period and adjuvant treatment were significantly associated with infection. The salvage treatment showed a success rate of 87.5% (7/8). Seven patients who received early aggressive salvage treatment recovered from infection. One patient with methicillin-resistant Staphylococcus aureus, who received salvage treatment 11 days after symptom onset, did not respond to drainage and antibiotic treatment. That patient subsequently underwent explantation. Conclusions In implant-based breast reconstruction, prevention of infection is of the utmost importance. However, if an infection is suspected, proactive empirical antibiotic therapy and collaboration with the necessary departments are required. Through a multidisciplinary approach and proactive early management, swift and appropriate salvage should be performed.